Pengembangan LKPD Berbasis Project Based Learning pada Mata Pelajaran IPAS Materi Membuat Peta Sederhana di Kelas IV SDN 24 Pontianak Tenggara - Cici Mirwanda; Siti Halidjah; Rio Pranata; Kartono Kartono (Departement of Mathematics Education, 2024)
This study aims to produce LKPD based on Project Based Learning in the subject of IPAS material on making simple maps in class IV SDN 24 Pontianak Tenggara. This research uses the Research and Development (RnD) research and development method with the ADDIE model. At the product trial stage, it was conducted in class IV of SDN 24 Pontianak Tenggara with 25 students. The results of this study are in the form of LKPD based on Project Based Learning in the subject of IPAS material on making simple maps. The results of the material validity test showed an average value of 3.49 by validator I and 3.40 by validator II with the criteria “Very Feasible”. The results of the language validity test showed an average value of 3.50 by validator I and 3.60 by validator II with the criteria “Very Feasible” and the results of the design validity test with an average value of 3.46 by validator I and 3.43 by validator II with the criteria “Very Feasible”. Small group learner response with an average score of 3.20 with the category “Good” and large group test with an average score of 3.79 with the category “Very Good”. Based on the results of the overall assessment, it is concluded that the Project Based Learning-based LKPD developed is very feasible to use in the IPAS learning process on the material of making simple maps in class IV SDN 24 Pontianak Tenggara.